Trade intermediation and the organization of exporters - Gabriel J. Felbermayr; Benjamin Jung (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2011)
The business literature and recent descriptive evidence show that exporting firms typically require the help of foreign trade intermediaries or need to set up own foreign wholesale affiliates. In contrast, conventional trade theory models assume that producers can directly access foreign consumers. This paper introduces intermediaries in an international trade model where producers differ with respect to productivity as well as regarding their varieties' perceived quality and tradability. We assume that trade intermediation is prone to frictions due to the absence of enforceable cross-country contracts while own wholesale subsidiaries require capital investment. We derive the sorting pattern of firms according to their degree of competitive advantage and show how the relative prevalence of intermediation depends on the degree of heterogeneity among producers, on the importance of market-specificity of goods, or on expropriation risk. We use US export data for 50 sectors and 133 destination countries to check the empirical validity of this predictions and find robust empirical support.
urn:nbn:de:bsz:21-opus-54263
Keywords: F12; F23; 330; Trade intermediation; international trade; heterogeneous firms; incomplete contracts